2021
DOI: 10.1111/jopy.12639
|View full text |Cite
|
Sign up to set email alerts
|

No relation of Need for Cognition to basic executive functions

Abstract: The investment trait Need for Cognition (NFC;Cacioppo & Petty, 1982;von Stumm & Ackerman, 2013) refers to relatively stable interindividual differences in the tendency to engage in and enjoy cognitively challenging tasks (Cacioppo et al., 1996). NFC has been examined in a large number of studies. Respective research has especially focused on its relations to individual differences in information processing (Cacioppo et al., 1996), to other cognitive (e.g., Fleischhauer

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 64 publications
(89 reference statements)
1
17
0
Order By: Relevance
“…This idea has been supported consistently by research showing that trait NFC had small but significant correlations with some cognitive capacity scores (Gauthier, Christopher, Walter, Mourad, & Marek, 2006;Hill, Foster, Sofko, Elliott, & Shelton, 2016), such as higher general, fluid, and crystalized intelligence (Hill et al, 2013), as well as giftedness, and markers of academic achievement (e.g., examination grades; Luong et al, 2017;Meier, Vogl, & Preckel, 2014). However, NFC has been shown to have zero or weak relations with rudimentary executive functioning domains, such as inhibitory control and working memory (Gartner et al, 2021). Beyond intellectual abilities, NFC concurs with individuals' propensity to expend their cognitive resources (von Stumm & Ackerman, 2013).…”
Section: Revised Manuscript (Clean Version)mentioning
confidence: 85%
“…This idea has been supported consistently by research showing that trait NFC had small but significant correlations with some cognitive capacity scores (Gauthier, Christopher, Walter, Mourad, & Marek, 2006;Hill, Foster, Sofko, Elliott, & Shelton, 2016), such as higher general, fluid, and crystalized intelligence (Hill et al, 2013), as well as giftedness, and markers of academic achievement (e.g., examination grades; Luong et al, 2017;Meier, Vogl, & Preckel, 2014). However, NFC has been shown to have zero or weak relations with rudimentary executive functioning domains, such as inhibitory control and working memory (Gartner et al, 2021). Beyond intellectual abilities, NFC concurs with individuals' propensity to expend their cognitive resources (von Stumm & Ackerman, 2013).…”
Section: Revised Manuscript (Clean Version)mentioning
confidence: 85%
“…This poses the question whether H-NFC individuals' higher reported self-control mirrors actual abilities or indicates a degree of overconfidence. The latter is highly probable, since a recent study found no association between NFC and performance in various tasks of executive functioning (Gärtner et al, 2021). This could be a potential pitfall for H-NFC individuals in situations where they reported high perceived control and self-efficacy, like smoking cessation, preventative health screenings, and health interventions with different message frames.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of NFC have a positive impact on performance ( Weissgerber et al, 2018 ) and school grades ( Grass et al, 2017 ; Luong et al, 2017 ; Strobel et al, 2019 ). Whereas some evidence exists for a positive link between NFC and cognitive ability (e.g., Fleischhauer et al, 2010 ; Hill et al, 2016 ), others have proposed that there is no such relationship (e.g., Gärtner et al, 2021 ). For example, Gärtner et al (2021) suggest that NFC is a trait that is less characterized by cognitive abilities per se , instead they rather stress that the degree of NFC is related to the willingness to invest effort and self-control in the task at hand (see also Sandra and Otto, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas some evidence exists for a positive link between NFC and cognitive ability (e.g., Fleischhauer et al, 2010 ; Hill et al, 2016 ), others have proposed that there is no such relationship (e.g., Gärtner et al, 2021 ). For example, Gärtner et al (2021) suggest that NFC is a trait that is less characterized by cognitive abilities per se , instead they rather stress that the degree of NFC is related to the willingness to invest effort and self-control in the task at hand (see also Sandra and Otto, 2018 ). Related to NFC, prior behavioral studies have reported that students with lower NFC have a tendency to prefer learning strategies characterized by surface rather than deep learning (e.g., Evans et al, 2003 ; Sandra and Otto, 2018 ), or lack engagement in cognitively demanding learning activities (e.g., Gärtner et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation